Kinematics of Active Deformation in the Malawi Rift and Rungwe Volcanic Province, Africa. (7th August 2019) - Ebinger, C. J.; Oliva, Sarah Jaye; Pham, Thi‐Quan; Peterson, Katherine; Chindandali, Patrick; Illsley‐Kemp, Finnigan; Drooff, Connor; Shillington, Donna J.; Accardo, Natalie J.; Gallacher, Ryan J.; Gaherty, J.; Nyblade, Andrew A.; et al.
Abstract: Although the deep, wide basins of the Western rift, Africa, have served as analogues for the evolution of half‐graben basins, the geometry and kinematics of the border, intrabasinal, and transfer fault systems have been weakly constrained. Despite the >100‐km‐long fault systems bounding basins, little was known of seismicity patterns or the potential for M > 7.5 earthquakes. Using our new local earthquake database from the 2013‐2015 Study of Extension and maGmatism in Malawi aNd Tanzania (SEGMeNT) seismic array (57 onshore, 32 lake‐bottom stations) and TANGA14 (13 stations), we examine the kinematics and extension direction of the Rungwe Volcanic Province and northern Malawi rift. We relocated earthquakes using a new 1‐D velocity model and both absolute and double‐difference relocation methods. Local magnitudes of 1, 178 earthquakes within the array are 0.7 < ML < 5.2 with a b ‐value 0.77 ± 0.03, and magnitude of completeness ML 1.9. Focal mechanism solutions for 63 earthquakes reveal predominantly normal and oblique‐slip motion, and full moment tensor solutions for ML 4.5, 5.2 earthquakes have centroid depths within 2 km of catalog depths. The preferred nodal planes dip more than 40° from surface to >25‐km depths. Extension direction from local earthquakes and source mechanisms of teleseismically detected earthquakes are approximately N58°E and N65°E, respectively, refuting earlier interpretations of a NW‐SE transform fault system. The low b ‐value indicating strong coupling across crustal‐scale border faults, border fault lengths >100 km, and evidence for aseismic deformation together indicate that infrequent M > 7.5 earthquakes are possible within this cratonic rift system. Key Points: Steep nodal planes of earthquake focal mechanisms correspond to projections of border and intrabasinal faults to depths of 25 km Extension direction across Rungwe volcanic province and Malawi rift is ENE, refuting interpretations of a NW‐SE transform fault system Low b ‐value, fault lengths >100 km, seismogenic layer 25‐30 km, and aseismic deformation suggest that infrequent M>7.5 earthquakes are possible